2017
DOI: 10.1007/s00415-017-8440-0
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of magnetic resonance findings in cerebrotendinous xanthomatosis: redefinition and evidence of new markers of disease progression

Abstract: Cerebrotendinous xanthomatosis (CTX) is a metabolic disease characterized by systemic signs and neurological impairment, which can be prevented if chenodeoxycholic acid (CDCA) treatment is started early. Despite brain MRI represents an essential diagnostic tool, the spectrum of findings is worth to be reappraised, and follow-up data are needed. We performed clinical evaluation and brain MRI in 38 CTX patients. Sixteen of them who were untreated at baseline examination underwent clinical and MRI follow-up after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 28 publications
0
38
0
2
Order By: Relevance
“…The study showed that the development of vacuoles was neither related to age nor to the extent of dentate nucleus hyperintensity. Cerebellar vacuolation was correlated to disability expressed by Rankin (RS) and Expanded Disability Status Scale (EDSS) and strongly to ataxia [15]. Accordingly, in our cohort, cases 1, 2, 6, and 7, who clinically had severe disability, showed marked vacuolation in cerebellar white matter.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…The study showed that the development of vacuoles was neither related to age nor to the extent of dentate nucleus hyperintensity. Cerebellar vacuolation was correlated to disability expressed by Rankin (RS) and Expanded Disability Status Scale (EDSS) and strongly to ataxia [15]. Accordingly, in our cohort, cases 1, 2, 6, and 7, who clinically had severe disability, showed marked vacuolation in cerebellar white matter.…”
Section: Discussionmentioning
confidence: 54%
“…Mignarri et al [15] suggested that cerebellar vacuolation with hypointensity in T2 and FLAIR images may be regarded as a biomarker of disease progression and unsatisfactory response to therapy. Besides, the absence of dentate nucleus signal alterations should be considered as an indicator of a better prognosis [15]. The study showed that the development of vacuoles was neither related to age nor to the extent of dentate nucleus hyperintensity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average diagnostic delay for CTX is estimated to 15 to 20 years, highlighting the need to improve clinical recognition . Brain MRI shows cortical and cerebellar atrophy, white matter signal alterations, and symmetric hyperintensities in the dentate nuclei . Plasma cholestanol levels are elevated and, together with low levels of bile alcohols in plasma or urine, are usually diagnostic.…”
Section: The “Top Ten” Of Treatable Iems Presenting With Movement Dismentioning
confidence: 99%
“…108 Brain MRI shows cortical and cerebellar atrophy, white matter signal alterations, and symmetric hyperintensities in the dentate nuclei. 109 Plasma cholestanol levels are elevated and, together with low levels of bile alcohols in plasma or urine, are usually diagnostic. Confirmation is obtained by sequencing of CYP27A1.…”
Section: #08 Cerebrotendinous Xanthomatosismentioning
confidence: 99%